Altered Spontaneous Brain Activity in Left-Behind Children: A Resting-State Functional MRI Study - Wang, Yu; Lu, Yi; Du, Meimei; Hussein, Nimo Mohamed; Li, Lan; Wang, Yu; Mao, Chuanwan; Chen, Tao; Chen, Fangfang; Liu, Xiaozheng; Yan, Zhihan; Fu, Yuchuan (Frontiers in Neurology, 2022)
Background Parental migration has been associated with a higher risk of cognitive and behavioral abnormalities in left-behind children (LBC). This study aimed to explore the spontaneous brain activity in LBC and reveal the mechanisms underlying behavioral and cognitive abnormalities. Methods Involved LBC (n = 36) and non-LBC (n = 22) underwent resting-state functional MRI (fMRI) examination and cognitive and behavioral assessment. The fMRI-based amplitude of low-frequency fluctuation (ALFF) and fractional ALFF (fALFF) were assessed to analyze the spontaneous brain activity pattern. The relationships among abnormal spontaneous brain activity, behavioral and cognitive deficits and altered family environment were assessed by partial correlation analysis. Results Compared with non-LBC, LBC exhibited increased amplitude of low-frequency fluctuations in the right lingual gyrus (LING), while a decreased ALFF was observed in the bilateral insula and right orbital part of the middle frontal gyrus (ORBmid) (two-tailed voxel-level p < 0.01 and cluster-level p <0.05, Gaussian Random Field (GRF) correction). The fALFF in LBC were significantly increased in the left cerebellum 9 (Cbe9) and right cerebellum Crus2 (CbeCru2), while it decreased in the right hippocampus and left superior temporal gyrus (STG) (two-tailed voxel-level p < 0.01 and cluster-level p < 0.05, GRF correction). The ALFF and fALFF values in abnormal brain regions were found to be correlated with the learning ability, except for the right insula, while the fALFF values of the left STG were positively correlated with the full-scale IQ scores (p < 0.05). Moreover, the ALFF and fALFF values in all abnormal brain regions correlated with the education level of caregivers (p < 0.05). Conclusions Our study provided empirical evidence that the lack of direct parental care during early childhood could affect brain function development involving cognition, behavior, and emotion. Our findings emphasized that intellectual and emotional cares are essential for LBC.